2021
DOI: 10.1021/acs.joc.1c02091
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) Iodide-Directed β-Mannosylation: Reaction Selectivity, Mode, and Application

Abstract: A direct, efficient, and versatile glycosylation methodology promises the systematic synthesis of oligosaccharides and glycoconjugates in a streamlined fashion like the synthesis of medium to long-chain nucleotides and peptides. The development of a generally applicable approach for the construction of 1,2-cis-glycosidic bond with controlled stereoselectivity remains a major challenge, especially for the synthesis of β-mannosides. Here, we report a direct mannosylation strategy mediated by ZnI 2 , a mild Lewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…To this end, we commenced our investigation by testing the feasibility of performing glycosylation reactions of three typical arabinofuranosyl donors ( 1a – 1c ) with glucosyl acceptor 2a under previously developed Zinc­(II) iodide-controlled 1,2- cis -glycosylation conditions (Scheme ). Results showed that tri- O -benzyl protected donor ( 1a ) afforded the desired product 3aa in good yield (80%), yet with poor stereoselectivity (α/β = 1:3), while the same reaction condition with known 3,5- O -TIPDS-protected donor ( 1b ) gave the almost exclusively arabinofuranoside 3ab with poor yield (35%), presumably due to low reactivity of the donor under ZnI 2 activation conditions. Interestingly, the moderate selectivity (α/β = 1:5) and acceptable yield (75%) of arabinofuranoside ( 3ac ) was obtained using the donor ( 1c ) equipped with the 3,5- O -xylylene-protected group, suggested that the donor ( 1c ) is a potentially stereocontrolled donor properly favoring 1,2- cis -β-Ara f products among the tested donors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we commenced our investigation by testing the feasibility of performing glycosylation reactions of three typical arabinofuranosyl donors ( 1a – 1c ) with glucosyl acceptor 2a under previously developed Zinc­(II) iodide-controlled 1,2- cis -glycosylation conditions (Scheme ). Results showed that tri- O -benzyl protected donor ( 1a ) afforded the desired product 3aa in good yield (80%), yet with poor stereoselectivity (α/β = 1:3), while the same reaction condition with known 3,5- O -TIPDS-protected donor ( 1b ) gave the almost exclusively arabinofuranoside 3ab with poor yield (35%), presumably due to low reactivity of the donor under ZnI 2 activation conditions. Interestingly, the moderate selectivity (α/β = 1:5) and acceptable yield (75%) of arabinofuranoside ( 3ac ) was obtained using the donor ( 1c ) equipped with the 3,5- O -xylylene-protected group, suggested that the donor ( 1c ) is a potentially stereocontrolled donor properly favoring 1,2- cis -β-Ara f products among the tested donors.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, our group discovered that zinc-directed stereocontrolled 1,2- cis -glucosylation/mannosylation (Figure a) . The catalysts hypothesized that the zinc cation coordinating the two-position of the donors and serving as a directing agent controls stereoselectivity for glycosylation enhanced by the fixed conformation of the pyranose ring.…”
Section: Introductionmentioning
confidence: 99%
“…As we have successfully developed a ZnI 2 -directed general strategy for 1,2-cis αglucosylation using a 4,6-O-naphthylidene and 2-O-benzyl (Bn)-protected glucosyl donors with excellent stereoselectivity [194], the ZnI 2 -mediated 1,2-cis glycosylation strategy has been applied to other linkages, such as 1,2-cis β-mannosides [217] and 1,2-cis αgalactosides [246]. In recent years, various methods have been developed [247][248][249] for stereoselective glycosylation to obtain more difficult 1,2-cis linkages with equatorial glycosides found in the core structure of the N-glycans [250][251][252][253][254][255][256][257].…”
Section: Zni 2 -Mediated 12-cis β-Mannosylation and Cis β-Galactosyla...mentioning
confidence: 99%
“…The alternative nucleophilic additive for α-glycosylation methyl (phenyl) formamide (MPF) was found and applied to the synthesis of α-(1,4)-glucosamine and α-(1,4)-galactosamine linkages (Figure 2A4) (Wang et al, 2020;. A simple ZnI 2 -directed strategy for 1,2-cis glycosylation bearing 4,6-O-tethered (Crich and Chandrasekera, 2004) glucosyl and mannosyl trichloroacetimidate donors has been developed with excellent stereoselectivity (Ding et al, 2021;Zhong et al, 2021). This simple strategy by the direction of SnCl 4 instead of ZnI 2 at −40 °C afforded 1,2-cis glycoside when 0.1 equivalent was used, and by using three equivalents of SnCl 4 at room temperature, we obtained 1,2-trans glycoside via product isomerization through plausible endo-cleavage supported by DFT calculations (Zhong et al, 2022).…”
Section: Recent Advances On 12-cis Glycosylations By Intermolecular C...mentioning
confidence: 99%